The Social, Civic, and Political Uses of Instagram in Four Countries - Shelley Boulianne; Christian P. Hoffmann (Journal of Quantitative Description: Digital Media)
Instagram has more than 1 billion monthly users. Yet, little is known about how citizens engage with this platform. We use survey data (representative on age and gender) to examine citizens’ Instagram use in four countries: the United States, Canada, the United Kingdom, and France (n=6,291). The survey was administered to an online panel matched to the age and gender profile of each country (September to November 2019). Across the four countries, about 40% of respondents used Instagram. This platform is especially popular among young adults who cultivate larger networks compared to older adults. Compared to older adults who use Instagram, younger users are more likely to follow a news organization. We employ these usage patterns to infer different motivations for use, drawing on the uses and gratification approach. We find that this approach is most useful for understanding cross-national and gender differences. In particular, Americans cultivate larger social networks on Instagram compared to citizens from other countries, implying greater social interaction motives. Males are more likely to follow news organizations compared to females, which implies they have more informational motives for Instagram use. Socioeconomic differences in Instagram adoption and types of uses are much smaller than the differences marked by age, gender, and country. This paper establishes the importance of Instagram use among citizens in four Western countries. Furthermore, we offer insights into the segments of the population that are intense users of Instagram, as well as different motivations for use.